2019
DOI: 10.1111/tid.13056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyoma viremia on 3‐year allograft kidney function

Abstract: Background Polyoma viremia is associated with damage to renal tubular and urothelial cells. This may imply that a certain level of viremia, even cleared thereafter, could be associated with long‐term renal dysfunction. Methods We, retrospectively, analyzed 390 first renal transplants adult recipients (≥18 years) who were monitored for BK viremia in the first 12 months and evaluated estimated GFR (MDRD‐4 equation) at 1 month and at the last follow‐up (959 ± 392 days). Results One hundred and ninety‐nine patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(81 reference statements)
1
2
0
Order By: Relevance
“…This is a relatively high incidence compared to the three large cohort studies mentioned above, where BKVN rates ranged from 0%-10%. [21][22][23] Whereas our association of biopsyproven BKVN with a decline in eGFR was somewhat expected, we also found that persistent BK viremia (reflected by participants that remained in the intensive phase) was associated with a decline in eGFR, consistent with some previous studies 1,30 but not others. 16,18,23 This is important when considering the design of future clinical trials of the antiviral therapy, since powering differences in BK viremia would require a smaller trial size than one with BKVN as the primary outcome.…”
Section: Discussionsupporting
confidence: 92%
“…This is a relatively high incidence compared to the three large cohort studies mentioned above, where BKVN rates ranged from 0%-10%. [21][22][23] Whereas our association of biopsyproven BKVN with a decline in eGFR was somewhat expected, we also found that persistent BK viremia (reflected by participants that remained in the intensive phase) was associated with a decline in eGFR, consistent with some previous studies 1,30 but not others. 16,18,23 This is important when considering the design of future clinical trials of the antiviral therapy, since powering differences in BK viremia would require a smaller trial size than one with BKVN as the primary outcome.…”
Section: Discussionsupporting
confidence: 92%
“…In a previous study, Hertz-Tang et al 24 found no significant increase in the risk of adverse outcomes including rejection, infection, and graft failure in patients with BK viremia in the absence of BKN compared to patients without BK viremia. In their study on 3-year graft function following BK viremia, David-Neto et al 25 found that only very high levels of viremia, those with viral loads compatible with presumptive or biopsy-proven BKN, lead to poor graft outcomes. Low and high levels did not.…”
Section: Discussionmentioning
confidence: 99%
“…Preemptive monitoring of BKPyV viral load by real-time polymerase chain reaction (RT-PCR) is essential for early diagnosis of BKPyV replication. Persistently elevated BKPyV viral loads exceeding 10 7 copies/mL in urine or 10 4 copies/mL in blood over a three-week period are highly associated with BKPyVAN risk [ 11 ]. Of note, while blood BKPyV monitoring is considered as routine practice by most transplantation centers, the significance of urine BKPyV monitoring is controversial.…”
Section: Introductionmentioning
confidence: 99%